Grade point average and teaching effectiveness - Tuliao, Alicia J. 1934- (s.n.], 1973)
This study ascertains whether there is a correlation between grade point average (GPA) and performance ratings of 45 teachers whose grade point average in college ranged from 1.0 to 1.75. The different items on the BPS Form 8-C were also determined. The analyses were based on the performance ratings of the 95 teachers who were rated by 50 principals and 15 head teachers.